International Tennis Federation (ITF), Women`s Tennis Association (WTA), and Association of Tennis Professionals (ATP) Expert Group Statement on Nutrition in High-Performance Tennis. Current Evidence to Inform Practical Recommendations and Guide Future Research - Vicente-Salar, N.; Celda, M. C.; Pluim, B. M.; Fernández-Fernández, J.; Stroia, K.; Ellenbecker, T.; Sanz, D.; Del Coso, J.; Moreno-Pérez, V.; Hainline, B.; López-Samanes, Á.; LaRoche, J.; et al. (International Journal of Sport Nutrition and Exercise Metabolism, 2025)
The sport of tennis involves unique nutritional demands for the physical and technical aspects of match play and training, as well as the nutritional challenges associated with extensive travel and a lengthy competition calendar. An expert group assembled by The International Tennis Federation, the Women`s Tennis Association, and the Association of Tennis Professionals has produced a scientific review of current evidence to inform practical recommendations for high-performance tennis. The narrative summary considers the diversity within the tennis community, including male and female players, youth players, and wheelchair players. The Expert Group Statement addresses nine specific topics: (a) introduction to tennis; (b) physiological characteristics of tennis training and match play; (c) training nutrition; (d) body composition, low energy availability, and relative energy deficiency in sport; (e) match-day nutrition; (f) dietary supplements for tennis performance; (g) environmental and travel issues; (h) nutrition guidelines during periods of illness and injury rehabilitation; and (i) special population groups. The statement advocates for an evidence-based approach to nutrition in high-performance tennis and emphasizes a "food first" philosophy, prioritizing food over supplements to meet nutrient requirements effectively. In recognition of the benefits of sound nutrition, strategies in supporting health and performance over a player`s career, academies, national federations, and international organizations are encouraged to engage professionals with appropriate nutrition-related qualifications and professional registrations to support players effectively.